Israel‘s Readiness for Health Emergencies - Navratil Van Praag, Alexandria Martinelli; Navratil, Vaclav; Navratil, Leos (Communications - Scientific letters of the University of Zilina, 2015)
Due to the geographic locations of Slovakia and the Czech Republic in Central Europe and the perceived threat of a mass terrorist act, along with the current economic climate, this article looks to determine the degree of readiness of both the Czech and Slovak Health Systems in addressing the impact of incidents in which there would be a large number of affected among population, particularly in cases where civilian contamination by any substance belonging to the group of CBRN (chemical, biological, radiological and nuclear agents) is minimal. Specifically, this article will inform readers about the readiness of State Health Services, in which the population is exposed to this risk for decades on end, and the number of victims of such attacks will be higher than ten thousand (10,000). As this model is one the State of Israel is accustomed to, all data from the Czech and Slovak Health Systems will be seen in reference to Israel’s performance, and further recommendations will be made where the Czech and Slovak Health Systems are found to be lacking.